Electrophysiological Characterization of "Giant" Cells in Stratum Radiatum of the CA3 Hippocampal Region - Savic, Natasa; Sciancalepore, Marina (Journal of neurophysiology, 2001)
Neuroscience Programme and Istituto Nazionale Fisica della Materia Unit, International School for Advanced Studies (SISSA), 34014 Trieste, Italy Savi , Nata a and Marina Sciancalepore. Electrophysiological Characterization of "Giant" Cells in Stratum Radiatum of the CA3 Hippocampal Region. J. Neurophysiol. 85: 1998-2007, 2001. Whole cell patch-clamp recording and intracellular staining with biocytin allowed the morphological and electrophysiological characterization of "giant" cells, studied in stratum (st.) radiatum of the CA3 region in 17- to 21-day-old rat hippocampal slices. These neurons had extensive dendritic arborization, a triangular soma, and a bipolar vertical orientation with axons directed to the pyramidal layer or extended into the st. oriens. Giant cells had significantly higher input resistance and shorter action potentials compared with CA3 pyramidal cells. Evoked action potentials were typically followed by an afterdepolarizing potential (ADP). During depolarizing current injection, most (80%) of recorded giant cells displayed a regular firing pattern (maximum steady-state firing rate, ~30 Hz) characterized by a modest early accommodation, whereas irregular firing was observed in the remaining 20% of giant cells. Hyperpolarizing current pulses induced a slow inward rectification of the electrotonic voltage responses, blocked by 2 mM external Cs + . N -methyl- D -aspartate (NMDA) and non-NMDA-mediated excitatory postsynaptic currents (EPSCs) measured under voltage clamp were distinguished on the basis of their voltage dependence and sensitivity to specific NMDA and non-NMDA glutamate receptor blockers. Non-NMDA EPSCs possessed a linear current-voltage relationship. EPSCs elicited by st. lucidum stimulation were reversibly reduced (mean, 23%) by the group II metabotropic glutamate receptor agonist (2S, 1'R, 2'R, 3'R)-2-(2,3-dicarboxyl-cyclopropyl)-glycine (DCG-IV, 1 µM). GABA A -mediated postsynaptic currents were subject to paired-pulse depression that was inhibited by the GABA B antagonist CGP 55845A (5 µM). We conclude that CA3 giant cells represent a particular class of hippocampal neuron located in st. radiatum that shares only some morphological and physiological properties with principal cells.